2006
DOI: 10.3201/eid1206.051451
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzaeType b Reemergence after Combination Immunization

Abstract: Combination vaccines may suppress Hib antibody concentration and avidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
17
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 18 publications
5
17
0
2
Order By: Relevance
“…It may therefore reflect a greater opportunity for natural boosting through carriage in the more recent cohorts who were followed up during a period of Hib resurgence. This result is supported by the findings of Johnson et al (11), who swabbed children before they received the booster and found a pharyngeal carriage rate of 2.1%, with a further 4.5% of children with high antibody levels suggestive of recent boosting through colonization. Studies of Hib antibody concentrations and disease incidence in adults over the period of 1991 to 2003 also suggest an important role for boosting through carriage in determining population immunity (16).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…It may therefore reflect a greater opportunity for natural boosting through carriage in the more recent cohorts who were followed up during a period of Hib resurgence. This result is supported by the findings of Johnson et al (11), who swabbed children before they received the booster and found a pharyngeal carriage rate of 2.1%, with a further 4.5% of children with high antibody levels suggestive of recent boosting through colonization. Studies of Hib antibody concentrations and disease incidence in adults over the period of 1991 to 2003 also suggest an important role for boosting through carriage in determining population immunity (16).…”
Section: Discussionsupporting
confidence: 79%
“…Johnson et al measured antibody concentrations in 2 to 4 year olds prior to their receiving a booster in the 2003 campaign; the GMC in DTwP/Hib recipients was 0.61 g/ml (95% CI, 0.41 to 0.92), compared with 0.30 g/ml (95% CI, 0.19 to 0.49) in DTaP/Hib recipients (11). These levels are remarkably close to those reported here.…”
Section: Discussionsupporting
confidence: 62%
“…It was also observed, in the Myanmar study, that anti-PRP antibody GMCs were considerably higher following DTPw-based Hib vaccinations, which we may attribute to the use of whole-cell pertussis, which was already known to elicit higher antibody titers than acellular pertussis (11). However, after the booster dose, these differences between vaccines were no longer present, in line with a recent study in which there was no association between postbooster anti-PRP antibody concentrations and the vaccine (DTPw/Hib and/or DTPa/Hib) used for primary vaccination (15). On the other hand, the DTPa/Hib Germany A and B studies demonstrated lower postbooster antibody levels for the DTPa/Hib combination than with separate administration (Table 2).…”
Section: Discussionsupporting
confidence: 66%
“…The United Kingdom's experience with Hib vaccine established the importance of a reduction in carriage (3,16,20) and induction of herd immunity in the long-term control of disease. MCC immunization has been shown to significantly reduce nasopharyngeal carriage of serogroup C meningococci (18) for at least 2 years with no evidence of serogroup replacement (19).…”
Section: Discussionmentioning
confidence: 99%